THE ROLE OF ANTHOCYANINS IN LIVING ORGANISMS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article highlights the chemical structure, synthesis, and specific properties of anthocyanins in color formation. In addition, the article provides information about the use of anthocyanins in the food industry and the field of medicine. The research results contribute to a deeper understanding of the practical importance of anthocyanins in plant ecology and human activity.